The concept of independent learning and KH. Ahmad Dahlan’s thought in education - Sijabat, Jenro Pandu; Rossa Bustam, Betty Mauli (Universitas Pendidikan Indonesia, 2022)
Abstract. This study discusses the similarities between KH Ahmad Dahlan’s educational thoughts through Muhammadiyah education and the concept of independent learning which was initiated by the Minister of Education, Culture, Research, and Technology, Republic of Indonesia, Nadiem Makarim. By using the library research method, the authors conclude that the educational thinking of KH. Ahmad Dahlan and the policy of the Minister, Nadiem Makarim, have several similarities, including: the existence of innovation in the substance-oriented curriculum of learning system, wanting an independent Indonesian education process, innovation from educational institutions to create human resources that have a direct positive impact on the progress of the nation and country, as well as creating competent human resources to respond to the challenges of the times.